MYTHIC PERSISTENCE AS PERFORMATIVE MEMORY: IRISH MYTHOLOGY IN THE PLAYS OF WILLIAM BUTLER YEATS - Zulqaynarova Parizoda Muhiddin qizi (International Journal of Literature and Language Studies, 2026)
The article analyzes the persistence of Irish mythology in William Butler Yeats plays. Although, Yeats is often discussed mainly as a poet, his dramatic works are central to his attempt to renew Irish cultural memory. In contrast, Irish myth in Yeats's drama does not simply survive as old subject matter; it becomes a living stage process through which ancient figures, ritual gestures, symbolic speech, and national memory are reactivated for modern audiences. Furthermore, this article proposes the notion of mythic persistence as performative memory. This notion means mythology persists when it is embodied again in performance, not only when it is retold in a written narrative. So, through plays such as Cathleen ni Houlihan, On Baile's Strand, Deirdre, The Green Helmet, and At the Hawk's Well, Yeats transforms Irish myth into dramatic form: the sovereignty figure becomes a political and spiritual symbol, Cuchulain becomes a troubled image of heroic Ireland, Deirdre becomes a figure of tragic selfhood, and the ritualized stage becomes a place where the past speaks to the present. In conclusion, Yeats's plays preserve Irish mythology by changing it; their power lies in their adaptation rather than repetition.